Programa “Cooperakids” para desarrollar la capacidad: Comunica su comprensión numérica, en una Institución Educativa Primaria -Trujillo, 2019 - Baltodano Contreras, Kimberli Jael (2021)
The objective of this research was to determine the influence of the "Cooperakids" Program in improving capacity: Communicates its numerical understanding in second grade students of primary education of the experimental educational center "Rafael Narváez Cadenillas", Trujillo-2019, for which a sample of 29 students of second degree "C" was used to whom the instrument was applied: "Test to determine the level of numerical comprehension", which was composed of 25 items and submitted to content validity by expert judgment and Cronbach’s alpha reliability with an acceptable level of reliability (0.753). The Programme had 16 learning sessions, which were implemented in approximately three months. After the application of the program to the experimental group, a significant improvement in the capacity "Communicates its numerical comprehension" was evident, as evidenced by the Student’s t test value, with a level of significance less than 5% (p< 0.05); therefore, it is concluded that the programme significantly improved the capacity "Communicates its numerical understanding".